Transformasi Digital Akuntansi Sebagai Strategi Dalam Manajemen Risiko Dan Penguatan Peran Generasi Z Dalam Membentuk Masa Depan Profesi - Darma Sanputra, Adrian Hartanto; Aprilia, Ervina Dwi; Salma, Ghina Mufidatus (Jayapangus Press, 2025)
This study aims to analyze the impact of digital transformation on risk management in accounting practices and the role of Generation Z in shaping the future of the accounting profession. The study uses a quantitative approach by distributing questionnaires to 217 accounting professionals and accounting students from various universities and companies in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results of the study indicate that digital readiness has a positive and significant effect on risk management (β=0.432, p<0.01), Generation Z competencies have a positive and significant effect on the adoption of accounting technology (β=0.387, p<0.01), and the implementation of new technology has a positive and significant effect on risk management effectiveness (β=0.512, p<0.01). Additionally, it was found that the adoption of artificial intelligence and blockchain has a significant impact on the development of new risk management strategies in accounting practice. This study contributes to the development of digital transformation literature in accounting and provides practical implications for accounting education and professional practice in preparing Generation Z workers to face technological changes.